Ending Social Promotion Without Leaving Children Behind The Case of New York City - McCombs, Jennifer Sloan; Kirby, Sheila Nataraj; Mariano, Louis T. (RAND Corporation, 2009)
The New York City Department of Education asked RAND to conduct an independent longitudinal evaluation of its 5th-grade promotion policy. The findings of that study, conducted between March 2006 and August 2009, provide a comprehensive view of the policy's implementation and its impact on student outcomes, particularly for students at risk of retention and those who were retained in grade.